1993
DOI: 10.1083/jcb.123.6.1345
|View full text |Cite
|
Sign up to set email alerts
|

Nup180, a novel nuclear pore complex protein localizing to the cytoplasmic ring and associated fibrils.

Abstract: Abstract. Using an autoimmune serum from a patient with overlap connective tissue disease we have identified by biochemical and immunocytochemical approaches an evolutionarily conserved nuclear pore complex (NPC) protein with an estimated molecular mass of 180 kD and an isoelectric point of •6.2 which we have designated as nupl80. Extraction of isolated nuclear envelopes with 2 M urea and chromatography of the solubilized proteins on WGASepharose demonstrated that nupl80 is a peripheral membrane protein and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 67 publications
(89 reference statements)
1
25
0
1
Order By: Relevance
“…The mass of the 55-kD plant GlcNAc protein (60 kD after 3H-galactose incorporation) raises the possibility that it may be the plant homolog of vertebrate p62. p62 is found in multiple copies on the cytoplasmic and/or the nucleoplasmic faces of the central NPC regions (Davis and Blobel, 1986;Dabauvalle et al, 1990;Cordes et al, 1991;Wilken et al, 1993). However, a monoclonal antibody against rat p62 (mAb414; Davis and Blobel, 1986) did not detect plant NPC proteins of similar mass (A. Heese-Peck and N.V. Raikhel, unpublished results).…”
Section: Proteins Modified By Glcnac Are Located At the Npcmentioning
confidence: 99%
“…The mass of the 55-kD plant GlcNAc protein (60 kD after 3H-galactose incorporation) raises the possibility that it may be the plant homolog of vertebrate p62. p62 is found in multiple copies on the cytoplasmic and/or the nucleoplasmic faces of the central NPC regions (Davis and Blobel, 1986;Dabauvalle et al, 1990;Cordes et al, 1991;Wilken et al, 1993). However, a monoclonal antibody against rat p62 (mAb414; Davis and Blobel, 1986) did not detect plant NPC proteins of similar mass (A. Heese-Peck and N.V. Raikhel, unpublished results).…”
Section: Proteins Modified By Glcnac Are Located At the Npcmentioning
confidence: 99%
“…Some authors have suggested that these cytoplasmic dots represent either AL (Greber et al 1990; Wozniak and Blobel 1992;Wilken et al 1993) or aggregates of nucleoporins (Carmo-Fonseca et al 1991). However, in these studies the cytoplasmic structures were not further characterized by electron microscopy, and thus the significance of this staining remained unknown.…”
Section: Introductionmentioning
confidence: 98%
“…This substance, which binds to O-linked N-acetylglucosamine moieties present on certain nucleoporins (45)(46)(47), effectively blocks receptor-mediated translocation (48 -52) but has little effect on the diffusion of intermediate-sized polymers and proteins (49,50,53). Electron microscopy studies indicate that wheat germ agglutinin accumulates mostly, although not exclusively, in the central region of the pores (52,54,55) and does not prevent binding of NLS-carrying cargoes to the surface of the pores (48, 52,56). The different effects exerted by wheat germ agglutinin on passive and facilitated transport through NPCs are naturally explained by the existence of separate routes of transport for each mode.…”
Section: Segregation Of Transport Modes In Nuclear Poresmentioning
confidence: 99%